A Solution to Combat Cybersecurity Threats Involving Big Data Analytics in the Hadoop Ecosystem - Lněnička, Martin; Čapek, Jan; Komárková, Jitka; Máchová, Renáta; Čermáková, Ivana (International Business Information Management Association-IBIMA, 2017)
Information and data security have become the biggest concern for almost all organizations. At the same time, new security challenges emerge constantly as networks become more highly distributed and virtualization architectures are adopted. Big data analytics promises to deliver opportunities for prevention and detection of advanced cyberattacks using internal and external big security data. The increase of these streamed and stored data together with the development of distributed analytical systems has led to rapid increase in demand for big data analytics integration in in the field of cybersecurity. Therefore, this paper attempted to discuss these practices. A literature review was conducted and the most suitable components were identified with the aim to propose a conceptual model, which should help to combat cybersecurity threats involving big data analytics in the Hadoop ecosystem. By implementing this model, organizations may be able to detect threats, create more defense mechanisms, and improve security of their infrastructure.
Řešení pro potírání kybernetických hrozeb založené na využití analýzy Big dat v Hadoop ekosystému
Keywords: Cybersecurity; big data analytics; Hadoop ecosystem; conceptual model; Kyberbezpečnost; analýza big dat; Hadoop ekosystém; konceptuální model